A Service-Oriented Autonomous Crane System - Xiong, Guangyu; Helo, Petri; Ekström, Steve; Shen, Zhen (IEEE, 2024)
The servicing of crane systems has been a major problem in the crane business value chain. The crane industry has been exploring well-defined solutions to solve problems on the customer's site. The service-oriented concept, empowered by artificial intelligence (AI) technology, has shown advantages in addressing issues in manufacturing. In this study, the authors propose a novel crane business model for the crane industry: a service-oriented autonomous crane system, which integrates advanced management concepts and AI-powered technology into the traditional industry-crane system. With the help of the novel business model, the crane industry and customers/users can benefit from an improvement in crane performance, and the model also offers further potential to promote problem-solving in the crane industry on the customer's site. From the perspective of knowledge development, this study gives a clear description of an intelligent service-oriented crane system. Crane stakeholders can develop their own customized autonomous crane systems based on the novel model with its technical structure. From the perspective of strengthening the crane business, the proposed model provides the foundation for developing smart solutions for the crane industry according to the specific requirements. From the perspective of scenarios applied to large construction machinery, the case study in this article provides a valuable reference for augmenting the servicing of large scale construction machinery.
Keywords: Artificial intelligence (AI)-powered technology; crane business value chain (CBVC); service-oriented autonomous crane system; social manufacturing concept; fi=Tuotantotalous|en=Industrial Management|